Catastrophic retroperitoneal hemorrhage in COVID-19 patients under anticoagulant prophylaxis - Amir Javid; Reza Kazemi; Mehdi Dehghani; Hossein Bahrami Samani (Urology Case Reports, 2021)
COVID-19 patients are at high risk for both capillary micro thrombi and large vessel thrombosis. Anticoagulant administration in COVID-19 patients, especially in ICU setting, is recommended by some researchers. However, clinical guidelines don't yet recommend anticoagulation therapies in therapeutic doses in these patients.In this article, we try to introduce a less known complication of heparin application in COVID-19 patients. Retroperitoneal hemorrhage when involves the psoas muscle might be deadly because of the large volume of bleeding before causing any significant alarm. It is very important to be careful in diagnosing and managing this complication.